The department team teaching assignment problem using zero-one integer programming / Syadatul Syaeda Mat Saleh, Najihan Awang@Ali and Nurul Husna Jamian - Mat Saleh, Syadatul Syaeda; Awang@Ali, Najihan; Jamian, Nurul Husna (UiTM Cawangan Perlis, 2020)
Nowadays, it is more important to be as efficient as possible. Most of the teaching institutions, one of the essential tasks that is carried out every year or every semester are to allocate teaching workload. Teaching workload allocation refers to the teaching staff teaches which subject and group classes. The task is a time-consuming process. The best allocation will be one of the contributing factors to the teaching quality. In current practice to this department, the teaching load allocates manually through a trial-and-error manner using Microsoft Excel. This may lead to unfavourable results. In this study, we aim to propose an innovative approach to allocate teaching load to group courses using integer programming which able to optimize the teaching allocation while satisfying the teaching staff preferences and based on department policies as constraints. Primary data were gathered using google form among 12 lecturers with 8 courses and 45 group classes considered. A feasible solution will be solved using LINGO unlimited software and the model serves as the best tool to assist the head of the department to allocate teaching workload. It found that the model proposes as a suitable tool to be employed for teaching allocation.